The Impact of the COVID-19 Pandemic on Education Financing - Al-Samarrai, Samer; Gangwar, Maulshree; Gala, Priyal (World Bank, Washington, DC, 2020)
The brief identifies the ways in which the COVID-19 (coronavirus) pandemic is likely to affect the availability of funding for education. It summarizes evidence on the negative impact that the pandemic is likely to have on education financing and identifies some policy responses to mitigate this impact.